2013
DOI: 10.1166/jnn.2013.6120
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Simulation Study on the Initial Stage of Si(001) Oxidation Under Biaxial Strain

Abstract: We have studied the very early stage of the room temperature oxidation of the externally-strained Si(001) surface using molecular dynamics simulation. It was found that the different treatment history of the sample under the same strain resulted in the difference in the number density of dimer. The as-prepared samples of different treatment history with 12.15% strain were used to investigate the initial oxidation behavior of Si(001). 500 times of independent deposition of single oxygen molecule onto the random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The formation of the oxide layer would subsequently hinder oxygen transport and prevent further oxidation, and the increase in temperature could promote the migration of oxygen to the deep Si layer. Cao et al [ 46 ] changed the surface dimer density of Si by biaxial tensile strain and revealed that the dimer plays an important role in the surface oxidation reaction by modifying the adsorption amount and penetration depth of O. Newsome et al [ 47 ] established a ReaxFF reaction force field of Si–Si, Si–O, and Si–H, and showed that SiC gradually transformed into silicon oxide and formed graphite-like layers. In the presence of excess O 2 , the graphite-like layer was further oxidized to CO and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the oxide layer would subsequently hinder oxygen transport and prevent further oxidation, and the increase in temperature could promote the migration of oxygen to the deep Si layer. Cao et al [ 46 ] changed the surface dimer density of Si by biaxial tensile strain and revealed that the dimer plays an important role in the surface oxidation reaction by modifying the adsorption amount and penetration depth of O. Newsome et al [ 47 ] established a ReaxFF reaction force field of Si–Si, Si–O, and Si–H, and showed that SiC gradually transformed into silicon oxide and formed graphite-like layers. In the presence of excess O 2 , the graphite-like layer was further oxidized to CO and CO 2 .…”
Section: Introductionmentioning
confidence: 99%